The Yanagita Kunio Guide to the Japanese Folk Tale (Indiana University Press, 1985)
This is the first English language translation of the Japanese classic Nihon mukashibanashi meii. The work remains the only single-volume reference available to the student of the Japanese folk tale. The author, Yanagita Kunio, was a prominent figure in early twentieth-century Japanese intellectual circles. The Guide is the result of thirty years of folk tale research by Yanagita, his colleagues, and his students. The editor, Fanny Hagin Mayer, having received encouragement and assistance from the late Yanagita Kunio, has brought the 347 folk tale types and the distribution of their variants into conformity with Japanese folk tale scholarship for the use of Western scholars. She has numbered the tale types in the Guide to facilitate reference to Ancient Tales in Modern Japan, the anthology of folk tales selected from the Guide. A complete bibliography of sources, several indexes, and maps have also been furnished by the editor.